(untitled) (Journal of Universal Science Research, 2023)
Modeling is one of the tools for cognition and study of phenomena, processes, and objects. This approach allows you to assess the current situation and make the most effective decisions. It also becomes possible to evaluate possible solutions without negatively impacting the current situation. Based on this, the work examines the key aspects of constructing a situational linguistic model in the context of the development of a pandemic. The Covid-19 pandemic is considered such a pandemic. A generalized concept of the situational-linguistic model of Covid-19 is presented.